PEMANFAATAN EKSTRAK KULIT BUAH MANGGIS (Garcinia mangostana L.) YANG MENGANDUNG TANIN DALAM MELINDUNGI PROTEIN AMPAS TAHU - KURNIAWAN .; A. SUNAKA; B.U.AS -SABA’IY; R. N. SIREGAR; I. HERNAMAN (Fakultas Peternakan Universitas Udayana, 2022)
The research objective was to determine the amount of tannin in mangosteen peel extract and the best dose of mangosteen peel extract in protecting tofu cake protein. Mangosteen peel flour is extracted using water at a ratio of 1: 5, 1:15, 1: 30, 1:45. Then mixed with the tofu cake and dried. Furthermore, in vitro testing was carried out using a completely randomized design followed by Duncan’s test. The study used 5 treatments by adding tofu pulp as a con- trol with each of which was repeated 4 times. The results showed that the mangosteen peel extract at a ratio of 1:45 produced the highest total tannins, namely 26.55g, and the lowest concentration of N-NH3 (P <0.05), namely 4.01 mM. Besides that, it also produced the lowest digestibility of dry matter and organic matter digestibility (P <0.05), with an average of 61.46% and 32%. The conclusion was that extraction at a ratio of 1:45 mangosteen peel flour and water produced the highest amount of dissolved tannins and resulted in the lowest N-NH3 value which can be used as a protein protection agent (bypass protein).